ESTIMATION OF GENETIC PARAMETERS FORPRE-WEANING GROWTH TRAITS IN TEDDY GOATS - Z. H. Kuthu; K. Javed; M. E. Babar; A. Sattar; M. Abdullah (Journal of Animal and Plant Sciences, 2017)
The objective of present study was to estimate genetic parameters of some pre-weaning growth traits in Teddy goats. Data available on 18702 kidding and performance records of 5150 Teddy goats and progeny of 382 sires maintained at three different locations(I) Livestock Experiment Station Rakh Ghulaman, District Bakkhar (1983-2008) (II) Livestock Experiment Station, Rakh Kharewala District Layyah (1971-2008) and (III) Livestock Experiment Station Chak Katora, District Bahawalpur (1975-2008) Punjab, Pakistan were analyzed for this purpose. Restricted Maximum likelihood (REML) procedure fitting an Individual Animal Model was used for variance component estimation. Estimates of breeding values for various performance traits like birth weight (BW), 60 day weight (60DW), weaning weight (WW), and pre-weaning daily gain (PrWDG) were calculated by using BLUP. For these purposes WOMBAT software was used. The heritability estimates for BW, 60DW, WW and PrWDG were 0.28±0.23, 0.26±0.44, 0.23±0.32, and 0.21±0.32, respectively, while the repeatability estimates for BW, 60DW, WW (as dam traits) were 0.53±0.02, 0.46±0.04, and 0.34±0.04, respectively. The increasing trend was observed in genetic trends for BW and WW during the period of study. It is envisaged from the present study that over the 34 years period selection remained ineffective to bring the desired changes and it will remain so if random use of breeding animals is practiced.
Keywords: Heritability; pre-weaning growth rate; post-weaning growth rate; genetic trend